Effect of different species of vesicular-arbuscular mycorrhizal fungi on nutrition and growth of cassava plants. - Kato, Osvaldo Ryohei; Oliveira, Elizabeth de; Santiago, Antonio Dias; Corrêa, Hélio (Pesquisa Agropecuaria Brasileira, 2014)
The effects of nine different species of vesicular-arbuscular mycorrhizal fungi on the nutrition and growth of cassava plants, were observed in a pot experiment carried out with sterile purple latosol soil, under greenhouse conditions. Shoot and root dry weights and N, P, K, Ca and Mg shoot contents as well as percentage root length colonization were evaluated. Final results revealed differential responses for the parameters evaluated, according to the inoculated specie of mycorrhizal fungi specie. Treatments inoculated with Glomus clarum, Entrophospora colombiana, and a mixture of the nine species studied presented the highest rates of root length colonization and dry matter production, and treatments inoculated with Acaulospora appendicula, Glomus clarum, and Entrophospora colombiana presented higher rates of P in the shoot